2014
DOI: 10.1002/nme.4772
|View full text |Cite
|
Sign up to set email alerts
|

Supremizer stabilization of POD–Galerkin approximation of parametrized steady incompressible Navier–Stokes equations

Abstract: In this work, we present a stable proper orthogonal decomposition-Galerkin approximation for parametrized steady incompressible Navier-Stokes equations with low Reynolds number. Supremizer solutions are added to the reduced velocity space in order to obtain a stable reduced-order system, considering in particular the fulfillment of an inf-sup condition. The stability analysis is first carried out from a theoretical standpoint and then confirmed by numerical tests performed on a parametrized two-dimensional bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
327
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 273 publications
(327 citation statements)
references
References 54 publications
0
327
0
Order By: Relevance
“…Finally, since the iteration count can be reduced to an extremely small amount, this methodology can be exploited to boost the convergence of iterative methods for other classes of parametrized problems, such as saddle-point problems, where the fine grid preconditioner cost per iteration may be particularly expensive. In this respect, suitable fine preconditioners trained for saddlepoint problems can be combined with RB coarse components tailored for solving parametrized saddle-point PDEs, as shown in [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since the iteration count can be reduced to an extremely small amount, this methodology can be exploited to boost the convergence of iterative methods for other classes of parametrized problems, such as saddle-point problems, where the fine grid preconditioner cost per iteration may be particularly expensive. In this respect, suitable fine preconditioners trained for saddlepoint problems can be combined with RB coarse components tailored for solving parametrized saddle-point PDEs, as shown in [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Also in the case of varying inflow velocities the ROM has demonstrated the ability of capturing the dependence of frequency of vortex shedding on the inflow velocity. As future developments the interest is into different efficient methodologies for the reconstruction of the pressure term and in particular to study the applicability of well known stabilization methods, used in the context of Galerkin ROM for finite elements [38,39], to a finite volume framework [45]. The interest is also in the study of the same physical problem, but where the fluid-structure interaction problem is also considered.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…Most ROM closure models have generally used some sort of stabilization procedure, e.g., [8][9][10]13,14,18,19,[21][22][23]48]. A physical motivation for this popular approach is given in [20], where it is shown that the concept of energy cascade is also valid in a POD setting.…”
Section: Approximate Deconvolution Rom (Ad-rom)mentioning
confidence: 99%
“…They generally fail, however, in the numerical simulation of convection-dominated flows [8][9][10][11][12][13][14][15]. Indeed, to ensure a low computational cost, only the first few POD modes are generally used in the ROM.…”
Section: Introductionmentioning
confidence: 99%